(untitled) (Economics and region, 2019)
The article is devoted to defining the concept of "financial security of the region"; the main indicators characterizing the financial security of Poltava region in the conditions of instability and economic crisis in the country; determination of financial security of Poltava region with integrated approach. The issue of ensuring the financial security of the region is quite urgent, due to the fact that current Ukrainian realities are characterized by macroeconomic, financial and political instability. The purpose of the work is to deep the theoretical foundations, consolidate the methodological approach and practical recommendations for improving the level of financial security of Poltava region. Objective: to research the essence of financial security of the region and to give its meaningful description; to characterize the integrated approach for determination of the level of financial security of the region; to analyze the financial security of Poltava region with an integrated approach. In the course of the research the following methods were used: theoretical generalization, comparative analysis, economic-statistical and graphical.